AN UPPER BOUND OF REAL ZEROS OF A RANDOM POLYNOMIAL (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
A new upper bound for the number of real zeros of a random algebraic polynomial with real coefficients is obtained. It is supposed that the coefficients are in dependent random variables identically distributed with expectation value zero, the variance and the third absolute moment being finite and non-zero.